2016
DOI: 10.1007/s13679-016-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant Menu Labeling Policy: Review of Evidence and Controversies

Abstract: In response to high rates of obesity in the USA, several American cities, counties, and states have passed laws requiring restaurant chains to post labels identifying the energy content of items on menus, and nationwide implementation of menu labeling is expected in late 2016. In this review, we identify and summarize the results of 16 studies that have assessed the impact of real-world numeric calorie posting. We also discuss several controversies surrounding the US Food and Drug Administration's implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 44 publications
3
85
0
Order By: Relevance
“…Further, there was only one real‐world, full‐service chain restaurant analysis with an adequate sample size, which found that calorie labeling was associated with a 150‐calorie reduction, but this study was limited by a cross‐sectional design . Although other reviews have concluded that menu labeling has little impact on fast‐food purchases , there is an extraordinary dearth of well‐designed and adequately powered studies to truly test this hypothesis in both fast‐food and full‐service chain settings.…”
Section: Discussionmentioning
confidence: 93%
“…Further, there was only one real‐world, full‐service chain restaurant analysis with an adequate sample size, which found that calorie labeling was associated with a 150‐calorie reduction, but this study was limited by a cross‐sectional design . Although other reviews have concluded that menu labeling has little impact on fast‐food purchases , there is an extraordinary dearth of well‐designed and adequately powered studies to truly test this hypothesis in both fast‐food and full‐service chain settings.…”
Section: Discussionmentioning
confidence: 93%
“…Promoting health via the information environment has been a key practice of health promotion practitioners, with examples that include inserting nutrition information in restaurant menus (59), installing seatbelt warning lights in the cars we drive (60), and delivering public service announcements via the television to promote parent–child communication about alcohol use (61). The concept of environmental print , which refers to the symbols, signs, numbers, and colors of everyday life that enhance children’s literacy (41, 62), holds relevance for harnessing the information environment by guiding health promotion practitioners to interweave health messaging across everyday-life contexts of individuals.…”
Section: Information Environmentmentioning
confidence: 99%
“…The average obscures differences by restaurant type and across individuals, an observation that is highlighted in this report. The most recent systematic review of field studies did not estimate an average treatment effect, but concluded that "the evidence regarding menu labeling is mixed, showing that labels may reduce the energy content of food purchased in some contexts, but have little effect in other contexts" (VanEpps et al, 2016). The consumer choice experiment in our study provides data on which type of context influences the effect of calorie-labeled menus.…”
Section: Abbreviationsmentioning
confidence: 64%
“…Numerous studies (and several systematic reviews) have tried to assess the effects of local menu labeling rules, but the results of the reviews have been mixed and sometimes contradictory (VanEpps et al, 2016;Sarink et al, 2016;Long et al, 2015;Sinclair, Cooper, and Mansfield, 2014;Swartz, Braxton, and Viera, 2011). There are plausible reasons for this heterogeneity, such as differences in label styles and information provided, differences in the types of restaurants in the study, and variance in groups of participants.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation